VD_FINDINFO Décision / 2015 / 86 vom 2. September 2014 - VD Tribunal cantonal (2014)
APPELCPP, RETRAITVOIE DE DROIT, INDEMNITÉEN GÉNÉRAL, DÉFENSE D'OFFICE | 135 CPP (CH), 386 al. 2 let. a CPP (CH), 428 al. 1 CPP (CH)